FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH TAHUN 2012-2017 - Eni Suharti; Ulfah Salpiah (JMB : Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine the effect of Capital Adequacy Ratio(CAR), Operational Income Operating Costs (BOPO) and NonPerforming Financing (NPF) on profitability (ROA) in Islamic CommercialBanks. This study uses a quantitative approach. The population in thisstudy were 13 Islamic Commercial Banks registered in the FinancialServices Authority (OJK). The sampling technique used was randomsampling, which is a Sharia Commercial Bank that is categorized asGood Financial Performance and Islamic Bank Category in 2017 andobtained a sample of 5 Islamic Commercial Banks. The analysistechnique used is multiple regression and hypothesis testing using tstatisticsto test partial regression coefficients and f-statistics to test thesignificance of the effects together. In addition, a classic assumption testis also conducted which includes normality test, autocorrelation test,heteroscedasticity test and multicollinearity test. The results of this studyindicate that partially CAR does not affect ROA in Sharia CommercialBanks, BOPO partially has a negative and significant effect on ROA inIslamic Commercial Banks , NPF partially has a negative and significanteffect on ROA in Islamic Commercial Banks. Simultaneously CAR, BOPOand NPF have a significant effect on the depedent variable (ROA) ofIslamic Commercial Banks.